Alfabetização científica e biotecnologia: o uso de metamodelos de linguagem e de metodologias ativas no ensino de Biologia - Cardôso, Helton Charllys Batista (2019)
Bringing biology classrooms closer to students' contexts and social practices may be the biggest challenge to be overcome by teachers in the coming decades. The use of active methodologies that enables the critical scientific understanding and stimulates curiosity and interest in scientific research should constitute one of the guiding axes of pedagogical actions in basic education, this approach is a goal to be achieved by the accomplishment of this work. In this perspective, the objective of this research was to analyze how the adoption of metamodels and active methodologies in biology teaching can contribute to improve the levels of learning about biotechnology in basic education. The work was developed with 52 students of the third year of high school in a public school in the state of Paraiba. Action research was adopted as a research strategy, which used questionnaires (pretest and posttest), focus group, in addition to participant observation to identify prior knowledge, indicators and the achieves pedagogical. The idea of metamodels was incorporated into the elaboration of the questionnaires and later it was used as an analysis tool to understand the learning styles of the students, the elaboration of the questionnaires and the focus group also incorporate the idea of levels and indicators of Scientific Literacy. The analysis of the pretests questionnaires was essential for the elaboration of didactic sequences, that adopted active methodologies as strategies to facilitate learning. The activities were evaluated continuously allowing a qualitative and comparative analysis between active methodologies and traditional methodologies to teach biotechnology in high school. The study revealed that the indicators of the language metamodels associated to the adoption of active methodologies were determinant for the students' involvement in all the activities carried out, as well as to consolidate knowledge and promote skills linked to the initial learning tendencies. The set of pedagogical actions carried out began to compose didactic pedagogical material, guiding the application of active methodologies, culminating in the elaboration of an educational website, thus contribution to the development of new pedagogical practices that are directly related to teaching of Biology with a scientific, contextualized and critical character.